Une « drôle de guerre » à l’écran : Khalkhin Gol - Alexandre Sumpf (Conserveries Mémorielles)
Shot in 1939 in Mongolia and edited in Moscow by documentary filmmaker Ilya Kopalin, Khalkhin Gol recounts the achievements of the Red Army and its commander General Zhukov in the struggle against the Japanese enemy. The film is striking for its hybridity, which is based on its multiple distribution objectives. First, it aims to mobilize the general public with the story of an absolute victory and the exaltation of the red soldier through a song written for the film, while serving as a tactical manual for unit leaders, particularly armoured units. The film must also plead with the supreme authorities the cause of a staff very heavily hit by the Great Terror. Finally, it must demonstrate to foreigners the Red Army's readiness and praise the Soviets' contribution to the local economy and human progress, while claiming that power is destined only for defensive warfare. Under the misleading appearance of a linear narrative, there is thus a complex mechanism that uses all the weapons developed by Soviet film propaganda from the previous two decades – in vain, it seems, since the film finally remains "on the shelf", considered inappropriate in 1940 when the "Strange peace" settles in the East of Europe.